ANALISA MANAJEMEN KAS KEUANGAN DESA BERBASIS DIGITAL EKONOMI PADA PELAKU USAHA KECIL DAN MENENGAH (UKM) & INDUSTRI KECIL DAN MENENGAH (IKM) KABUPATEN BOGOR - Sri Setiawati (POLITEKNIK LP3I JAKARTA, 2018)
Abstract The high consuming growth supported by the ease of transaction push the consumer to have services and goods. Digital economy offered ease in transaction not only the finance system, payment system, cyber security, integrity but also secure in finance transaction. The aim of this study is to know the role of community in supporting, building, and developing the Small & Medium Enterprises; and Small & Medium Industry in empowering the people’s economy. Quantitative is used as the method by collecting data through case study, observing, field and library research. the result showed that Small & Medium Enterprises; and Small & Medium Industry have a low cashflow which is proven from the low of liquidity of the income. Therefore, there must be a special role from the local government, cooperative, industrial, and trade service in guiding the cash management for the Small & Medium Enterprises; and Small & Medium Industry doer in order to increase its’ program. Keywords: Cash Management, Digital Economy, Small and Medium Enterprises, and Small and Medium Industry Doer.